The Role of a Gadget-Free Community Program in Improving Elementary School Children’s Social Skills - Gunarti Dwi Lestari; Desika Putri Mardiani; Nunuk Hariyati; Rofik Jalal Rosyanafi; Rivo Nugroho; Danang Prastyo; Fonny Dameaty Hutagalung (International Journal of Learning Reformation in Elementary Education, 2026)
The increased use of digital devices among elementary school children often results in decreased direct interaction, collaborative skills, and emotional regulation abilities. Kampung Lali Gadget (KLG or a Gadget-Free Community), a community-based community in Sidoarjo, presents a form of non-formal education through traditional game activities integrated with the values of collaboration, empathy, and social communication. This study aims to understand in depth the role of the KLG community in shaping and strengthening the social skills of elementary school-aged children. The method used is qualitative research with a case study approach. Data were collected through participant observation during traditional game sessions, in-depth interviews with children, parents, facilitators, and community leaders, and documentation of activities. Data analysis was conducted using thematic techniques through the stages of data reduction, data presentation, and conclusion drawing, as well as triangulation of sources and methods to maintain validity. The results of the study indicate that children's involvement in KLG activities facilitates meaningful social learning processes: children become more skilled at communicating, showing empathy, collaborating, following rules, and managing emotions in group interactions. The role of community facilitators using a reflective and collaborative approach proved crucial in creating a safe, inclusive, and enjoyable learning environment. Furthermore, parental participation and local community support contributed to the program's sustainability. This study concludes that KLG functions as a culturally based communal learning space that is effective in improving the social skills of elementary school children.